The role of Langerhans cells in pathologies of the skin. Issue 8 (8th May 2019) - Rajesh, Aarthi; Wise, Lyn; Hibma, Merilyn
Abstract: Langerhans cells (LCs) are epidermal immune cells of myeloid origin. Although these cells were primarily thought to play a defensive role in the skin, evidence now indicates a diverse range of LC‐mediated effects including the relay of viral antigens in herpes simplex infection, recruitment of eosinophils in atopic dermatitis and promotion of a Th17 response in Candida infection. LCs may have a protective or suppressive function in pathologies of the skin, with differing functions being driven by the skin milieu. Understanding LC function will help guide the development of interventions that modulate these cells for therapeutic benefit. Abstract : Langerhans cells (LCs) are skin immune cells that are functionally diverse in a range of pathologies. This review provides an overview of the immune activating and suppressing functions of LCs in infectious and inflammatory disease, cancer and in wound healing.